2015
DOI: 10.1136/tobaccocontrol-2014-051993
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reaction facilitates the brain and behavioural impact of graphic cigarette warning labels in smokers

Abstract: Background Warning labels on cigarette packages are an important venue for information about the hazards of smoking. The 2009 US Family Smoking Prevention and Tobacco Control Act mandated replacing the current text-only labels with graphic warning labels. However, labels proposed by the Food and Drug Administration (FDA) were challenged in court by the tobacco companies, who argued successfully that the proposed labels needlessly encroached on their right to free speech, in part because they included images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 61 publications
11
71
0
Order By: Relevance
“…These findings are consistent with previous observational research on the impact of pictorial warnings on adolescents [8], in which unaided recall of the warning [15] and social interactions [14] increased following national implementation of pictorial warnings on cigarette packs in the United Kingdom and Australia, respectively. Some experimental research with adolescents has also demonstrated stronger negative emotional reactions to pictorial warnings [27,28], a construct hypothesized to explain the effect of pictorial warnings on attitudes and behavior [29]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous observational research on the impact of pictorial warnings on adolescents [8], in which unaided recall of the warning [15] and social interactions [14] increased following national implementation of pictorial warnings on cigarette packs in the United Kingdom and Australia, respectively. Some experimental research with adolescents has also demonstrated stronger negative emotional reactions to pictorial warnings [27,28], a construct hypothesized to explain the effect of pictorial warnings on attitudes and behavior [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Similar to implicit methods, neuroimaging is more sensitive than self-report to the neurophysiological mechanisms underlying the effectiveness of information delivery. Recent functional magnetic resonance imaging data showed that the FDA graphic warnings that were rated higher in emotional reaction had greater neural activation in brain regions related to emotional memory (Wang, Lowen, Romer, Giorno, & Langleben, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The study conducted to inform the U.S. Food and Drug Administration’s (FDA) selection of the final graphic warnings utilized self-reported emotional and cognitive reactions, recall, beliefs about the health risks of smoking, and intention to quit as outcomes, which are all explicit measures (Nonnemaker, Choiniere, Farrelly, Kamyab, & Davis, 2015). One small experimental study reported that exposure to the graphic warning labels that were high in emotional reactivity reduced the electrophysiological brain response to smoking cues (Wang, Lowen, Romer, Giorno, & Langleben, 2015), but other recent studies on the impact of the FDA’s final proposed graphic warnings have relied on self-reported explicit outcome measures (Cameron, Pepper, & Brewer, 2013; Cantrell et al, 2013; Hammond, Reid, Driezen, & Boudreau, 2013; Mays et al, 2014; Nonnemaker et al, 2015; Villanti, Cantrell, Pearson, Vallone, & Rath, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Morris et al (1998) showed that amygdala activation occurred when subjects were exposed to human faces with emotions such as fear or suffering. Several recent studies found that the amygdala responds robustly to the presentation of pictorial HWLs (Jasinska et al , 2012; Newman-Norlund et al , 2014; Wang et al, 2015). Other research suggests that the amygdala’s response to emotional stimuli is predictive of a wide variety of behavioral outcomes including post-exposure memory (Canli et al , 2005).…”
Section: Introductionmentioning
confidence: 99%